Feminist imagination : genealogies in feminist theory - Bell, Vikki, 1967- (Theory, culture & society., 1999)
"Vikki Bell provides a compelling rethinking of feminist theory as bound up with attempts to understand oppression outside a focus on 'women'. She affirms feminism as a site and mode of making these connections."--Jacket